Nano-diammonium phosphate enhances grain yield by modulating gas exchange traits and nutrient use efficiency in rice - Sweety, R R B; Boominathan, P; Senthil, A; Jegadeeswari, D; Kumar, G P (Plant Science Today, 2025)
Nutrients are primarily applied to crops through the soil to enhance productivity while maintaining crop and soil health. However, high doses of soil -applied nutrients often reduce nutrient use efficiency, increase cultivation costs, and contribute to environmental pollution. With their high surface area to volume ratio, nano-formulated nutrients have emerged as effective alternatives, requiring lower doses and demonstrating superior nutrient use efficiency (NUE) compared to conventional fertilizers. This experiment was conducted to study the influence of nano diammonium phosphate (nano-DAP) on physiological and yield-associated traits in rice and to assess the extent of replacement of soil application of nitrogen (N) and phosphorous fertilizers with foliar application of nano-form of DAP. Field trials included nine treatments, comprising 50% and 75% of the recommended dose of nitrogen and phosphorus (RDNP) and 100% of the recommended dose of fertilizers (RDF), and foliar application of conventional and nano-DAP. Foliar treatments were applied during the active tillering and panicle initiation stages. Among the treatments, 75% RDF and two foliar sprays of nano-DAP performed better in terms of morpho-physiological parameters, particularly leaf area, dry matter production, photosynthetic rate, stomatal conductance, and number of productive tillers compared to 100% RDF. Furthermore, the NUE of nano-DAP treatments was significantly higher, reflecting an improved ability of the rice plants to utilize the nanoform nutrients, resulting in enhanced yield effectively.